2010
DOI: 10.1089/neu.2009.0982
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Regional Changes after Focal Traumatic Brain Injury

Abstract: Magnetic resonance imaging (MRI) is widely used to evaluate the consequences of traumatic brain injury (TBI) in both experimental and clinical studies. Improved assessment of experimental TBI using the same methods as those used in clinical investigations would help to translate laboratory research into clinical advances. Here our goal was to characterize lateral fluid percussion-induced TBI, with special emphasis on differentiating the contused cortex from the pericontusional subcortical tissue. We used both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 37 publications
3
35
0
Order By: Relevance
“…The patterns of T 2 , ADC, and FA changes after TBI are in general agreement with those reported from our previous studies 8,36 and other studies. [37][38][39] In the impacted region (R0I-1), average CBF reached ischemic levels (⩽20% of normal) at 1 and 3 hours, which is expected to cause ischemia and to manifest in detectable T 2 and ADC changes as observed. Interestingly, at 14 days there were no apparent large infarcts detected based on MRI and behavioral scores indicating that outcome measures were returning toward normal, consistent with our previous study.…”
Section: Cortical Blood Flowmentioning
confidence: 97%
“…The patterns of T 2 , ADC, and FA changes after TBI are in general agreement with those reported from our previous studies 8,36 and other studies. [37][38][39] In the impacted region (R0I-1), average CBF reached ischemic levels (⩽20% of normal) at 1 and 3 hours, which is expected to cause ischemia and to manifest in detectable T 2 and ADC changes as observed. Interestingly, at 14 days there were no apparent large infarcts detected based on MRI and behavioral scores indicating that outcome measures were returning toward normal, consistent with our previous study.…”
Section: Cortical Blood Flowmentioning
confidence: 97%
“…The mean local diffusion coefficient of water, or apparent diffusion coefficient (ADC), can be estimated from a set of images with different b values. According to this definition, the ADC decrease observed in abnormal brain tissue is ascribable to cellular swelling (or cytotoxic edema), in which water shifts from the extracellular to the intracellular compartment because of disturbances in ion homeostasis (Lescot et al, 2010).…”
Section: Magnetic Resonance Measurementsmentioning
confidence: 99%
“…First, a fast multi-slice TURBO RARE T2-weighted sequence was used to check that the positioning of the animals was accurate and reproducible for repeated measurements as well as to assess the positioning of the voxels used for localized 1 H-MRS. The TURBO RARE sequence parameters were as follows: repetition time (TR) ¼ 1.93 s; echo time (TE) ¼11.7 ms; RARE factor¼8; field of view (FOV)¼35 Â 35 mm; in-plane resolution ¼256 Â 256 pixels in 17 transverse slices; slice thickness¼1.3 mm; and acquisition time¼ 46 s. Given the short echo time, these T2 images had a high signal-to-noise ratio (Lescot et al, 2010).…”
Section: T2 Imagingmentioning
confidence: 99%
“…In addition, a much smaller but statistically significant decrease of NAA was observed in the contralateral side, suggesting a global NAA disturbance. Although sharp decrease of NAA immediately after TBI has not yet been fully understood, it may be due to impaired NAA synthesis in the mitochondria (Bates et al, 1996;De Stefano et al, 1995;Lescot et al, 2010;Schuhmann et al, 2003;Signoretti et al, 2008). The nervous system-specific metabolite NAA is synthesized from aspartate and acetyl-coenzyme A, relies on ATP, through the action of L-aspartate N-acetyltransferase in mitochondria or through the cleaving of N-acetyl-aspartyl-glutamate by Nacetylated-a-linked-amino dipeptidase, along with glutamate (Baslow, 2003).…”
Section: Xu Et Almentioning
confidence: 99%
“…As shown in human TBI studies, the metabolic changes in TBI brain may occur over weeks to months following TBI, and these changes may persist for several years post-injury in humans (Brooks et al, 2000;Friedman 1999;Ross et al, 1998). Previous in vivo 1 H MRS studies in various rat model injuries also indicated a time evolution of TBI (Lescot et al, 2010;Schuhmann et al, 2003;Vagnozzi et al, 2007). Schuhmann and colleagues (2003) showed that tCr, NAA, glutamate (Glu), and Cho concentrations significantly decreased during the first 24 h, and then started to increase at 7 days in a controlled cortical impact (CCI) model.…”
Section: Introductionmentioning
confidence: 99%